IL-36 receptor is expressed by human blood and intestinal T lymphocytes and is dose–dependently activated via IL-36β and induces CD4+ lymphocyte proliferation - Penha, Rafael; Higgins, John; Mutamba, Shilla; Barrow, Paul; Mahida, Yashwant R.; Foster, Neil (Elsevier, 2016)
We show that IL-36R is expressed by T (CD4+ and CD8+) and B (CD19+) lymphocytes in human blood and also by CD4+ T lymphocytes in the intestinal lamina propria. IL-36R protein was mostly stored in the cytoplasm of CD4 lymphocytes and B cells, during steady state conditions and the greatest expression of IL-36R mRNA was measured in CD4+ (T helper) lymphocytes. IL-36 β, which functions via IL-36R induced rapid and significant (P < 0.05) proliferation of CD4+ lymphocytes, within 48 h. IL-36R expression was also maintained on the surface of circulating CD4+ lymphocytes which enter the intestinal lamina propria.